2020
DOI: 10.1111/ijcp.13609
|View full text |Cite
|
Sign up to set email alerts
|

Decreased left atrial appendage emptying velocity as a link between atrial fibrillation type, heart failure and older age and the risk of left atrial thrombus in atrial fibrillation

Abstract: Introduction: Decreased left atrial appendage emptying velocity (LAAV) is a known predictor of LAA thrombus in atrial fibrillation (AF). The aim of our study was to identify which of the clinical risk factors for LAA thrombus are associated with decreased LAAV. Methods: The study included 1476 consecutive AF patients who underwent transesophageal echocardiography (TEE) before AF direct current cardioversion or ablation in two high-reference cardiology departments. Patients were divided into two groups: 71 (4.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…HF is a component of all thromboembolic risk scores. [19] In our study, patients with LAAT significantly more often had HF. In the univariable logistic regression analysis, it was a strong predictor of LAAT both in men and women.…”
Section: Discussionsupporting
confidence: 45%
“…HF is a component of all thromboembolic risk scores. [19] In our study, patients with LAAT significantly more often had HF. In the univariable logistic regression analysis, it was a strong predictor of LAAT both in men and women.…”
Section: Discussionsupporting
confidence: 45%
“…Compared with younger patients, Ilercil [25] found that older patients had lower LAAV despite higher LVEF, smaller left ventricle size, and similar LA and LAA volumes. Gawałko's study [24] showed that age>65 years independently related to LAAV<20 cm/s. Female gender is one variable in CHA2DS2-VASc score, which represents the risk of stroke for AF.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with AF, especially persistent AF have longer AF duration, more severe AF burdens and LA structural remodeling [29] and thus probably associate with lower LAAV. Gawałko's study [24] showed that non-paroxysmal AF might increase LAA thrombus risk via reduced LAAV. Age is an independent risk factor for thromboembolism in AF and a few studies have found that LAAV decreases with age [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Using the LAAEV as a marker for inactive LAA, our study found that a value of 25 cm/sec was the cut-off point for inactive LAA, which is consistent with Mukhopadhyay et al [29], who studied 100 patients with severe rheumatic mitral stenosis to determine the prevalence of inactive LAA, but this value is higher than Gawako et al who defined the cut-off value of LAAEV to be 20 cm/sec, which could be a factor in predicting inactive LAA. Nonetheless, this difference could be an indicator of a different pathology [30]…”
Section: Discussionmentioning
confidence: 99%